Multiscale crystal plasticity finite element model for investigating the irradiation hardening and defect evolution mechanism of A508-3 steel - Pandong Lin; Junfeng Nie; Meidan Liu (Nuclear Materials and Energy, 2022)
A multiscale crystal plasticity finite element model, which combines molecular dynamics with crystal plasticity theory, is proposed. In this model, the evolution equations for partial- and full-absorption dislocation loops are utilized. Furthermore, we introduce the absorption probability in the crystal plasticity framework using the parameters at the atomic scale, which connects the microscale and mesoscale. The proposed method is applied to analyze the mechanical behavior of irradiated body-center-cubic (BCC) A508-3 steel. It was found that the numerical results agree well with the experimental data, which demonstrates the feasibility and accuracy of this model. Irradiation hardening was captured by the proposed model. Considering parameter evolution, irradiation can accelerate the increase in mobile dislocations and impede the decrease of immobile dislocations. The proposed model may provide a theoretical guide for predicting the mechanical behaviors of irradiated BCC metals for the selection of structural materials in nuclear plants.